PENERAPAN METODE PEMBELAJARAN SIMULASI PADA MATA PELAJARAN PAI KELAS VIII DI SMPN 3 SONGGON SATU ATAP - Ahmad Izza Muttaqin; Endhang Suhilmiati; Abul Hasan Asy Syadzali (MUMTAZ : Jurnal Pendidikan Agama Islam, 2021)
This study aims to explain the application of the simulation learning method to Islamic Education Class VIII subjects at SMPN 3 Songgon One Roof for the 2020/2021 academic year, to explain the inhibiting factors or obstacles in the application of the simulation learning method to PAI subjects Class VIII at SMPN 3 Songgon Satu Roof Years. 2020/2021 lessons.The type of research used in this research is descriptive qualitative. Methods of data collection using observation techniques, interviews, and documentation. The research subjects or respondents in this study were PAI teachers, school principals, and eighth grade students. The validity of the data is done by triangulation of sources. Data analysis includes data collection (data collection), data reduction (data reduction), data display (data display), and conclusion drawing. The results of the study explain that PAI teachers at SMPN 3 Songgon Satu Roof in learning planning, teachers prepare learning tools such as lesson plans, syllabus, attendance, and teaching journals. In addition, in the implementation of this simulation method, the simulation was started by a group of actors, other students followed attentively, the teacher provided assistance to actors who had difficulties. For evaluation/assessment, namely conducting discussions both about the course of the simulation and the material of the story being simulated. The teacher must encourage students to provide criticism and responses to the simulation implementation process, then the teacher formulates conclusions, besides that the teacher provides remedial or value improvements for students whose scores are less than the KKM.